hilarious, heartwarming, and wholesome as heek: bookshops & bonedust - Baldree, Travis; Travis Baldree (New York Tor publishing group, 2023)
Bookshops & Bonedust by Travis Baldree is a cozy high-fantasy prequel to Legends & Lattes. It follows a young, wounded orc mercenary named Viv, who is forced to recuperate in the sleepy beach town of Murk, where she discovers a love for books, forms new friendships, finds romance, and accidentally uncovers a dark, necromantic mystery.
English